Generalized lichen nitidus in a 5-year-old girl. - Sequeira, E.V.; Ballal, S. (European Journal of Pediatric Dermatology, 2024)
Lichen nitidus is a rare dermatitis characterized by pathognomonic skin and histological lesions, in the absence of a precise cause, although its relationship with lichen planus has long been discussed. The generalized form is even rarer and can affect the nails and mucous membranes. A case was described in a 5-year-old girl.